The aspect ratio effect of drug nanocrystals on cellular internalization efficiency, uptake mechanisms, and in vitro and in vivo anticancer efficiencies1. Issue 8 (28th February 2015) - Tian, Baishun; Zhang, Xiujuan; Yu, Caitong; Zhou, Mengjiao; Zhang, Xiaohong
<x xml:space="preserve">Abstract</x> The aspect ratio effect of drug nanocrystals on their in vitro cellular internalizing efficiency and in vivo antitumor efficiency was investigated.